Papua New Guinea : The World Bank Group Country Opinion Survey FY 2014 - World Bank Group (World Bank, Washington, DC, 2015)
The Country Opinion Survey in Papua New Guinea assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Papua New Guinea perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Papua New Guinea on 1) their views regarding the general environment in Papua New Guinea; 2) their overall attitudes toward the WBG in Papua New Guinea; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Papua New Guinea; and 4) their perceptions of the WBG’s future role in Papua New Guinea.